STRATEGI PEMBELAJARAN PAI DALAM KONTEKS IMPLEMENTASI NILAI-NILAI RELIGIUS DI SMP ALAM BANYUWANGI ISLAMIC SCHOOL - Miftahul Alimin (LP2M Universitas Ibrahimy, 2020)
The learning strategy is one of the important components in Islamic education learning. In embedding religious values, a competitive learning strategy is needed so that the objectives of Islamic Education can be realized. SMP Alam Banyuwangi Islamic School is one of the education institutions that apply a special system in learning with a boarding school approach. Through a philosophical approach, this research focuses on uncovering the types of learning strategies at SMP Alam Banyuwangi Islamic School and their implementation in learning in the context of cultivating religious values. The researcher chooses the type of qualitative research in presenting the data according to the research focus with historical, philosophical and theological approaches descriptively. Based on the data and analysis in this research, it can be concluded that Islamic education learning strategy in SMP Alam Banyuwangi Islamic School uses a Contextual Teaching Learning (CTL) approach based on multiple intelligence with the category of student-centered learning strategies (Student Center Strategies). In addition, in the process, the implementation of Islamic education learning strategy at SMP Alam Banyuwangi Islamic School is actualized in three stages of learning. They are: pre instructional in the form of a learning design formatted in the RPP PAI material, vision, and mission of SMP Alam Bnyuwangi Islamic School; learning activities use the actualized R.U.P.E system with several activity formats; and the evaluation also uses the R.U.P.E system, whose assessment accumulates all learning activities that have been designed at SMP Alam Banyuwangi Islamic School.